DEVELOPMENT OF LEARNING MEDIA OF AUGMENTED REALITY APPLICATION IN BASIC BUILDING CONSTRUCTION LESSON - Rosmawita Saleh; Hertia Lestari; R. Eka Murtinugraha (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
An augmented reality is a technology that will be utilized at Basic Building Construction lesson in the Construction and Property Business Expertise Competency at SMK Negeri 1 Cibinong as a learning media to enhance comprehension of building construction material and modify learning media to technology advancements. This research was conducted with Research and Development (R&D) method and the ASSURE model. In this research, the process of developing learning media encompassed various steps, including analysis, determining a learning method, identifying a learning objective, constructing the media and materials, participation, and evaluation and improvement. The research results indicated that: (1) media experts’ validation attains an average of 91% (very feasible); (2) material experts’ validation attains a percentage of 92% (very feasible); and (3) augmented reality application users’ validation attains an average result of 81% (very feasible). The augmented reality application in the Basic Building Construction lesson can be utilized in the Construction and Business Expertise Competency at SMK Negeri 1 Cibinong, as determined by the validity test and the limited user trials.